A retrospective study of cryopreserved umbilical cord as an adjunctive therapy to promote the healing of chronic, complex foot ulcers with underlying osteomyelitis. Issue 5 (30th September 2016) - Caputo, Wayne J.; Vaquero, Carina; Monterosa, Alexis; Monterosa, Patricia; Johnson, Edward; Beggs, Donald; Fahoury, George J.
Abstract: Complex lower extremity ulcers with exposed bone, tendon, muscle, and/or joint capsule as well as multiple comorbidities including diabetes, ischemia, and underlying osteomyelitis are difficult to heal and associated with high morbidity and mortality and high rates of amputation. A retrospective review was performed to assess healing of 31 patients presenting with 33 complex foot ulcers with a confirmed histopathological diagnosis of osteomyelitis treated by the same surgeon at a single wound care center by the following treatment regimen: sharp debridement, resection of infected bone when necessary, open cortex, antibiotics, and application of cryopreserved umbilical cord (cUC). The average ulcer size was 15.6 ± 17.7 cm 2 (0.4–73.95 cm 2 ). Overall, 26 out of the 33 wounds achieved complete closure (78.8%). Five patients were lost to follow‐up and one patient expired during the course of treatment, not believed to be treatment related. Of the remaining 27 wounds in patients not lost to follow‐up, 26 achieved complete healing with an average time to healing of 16 weeks and an average of 1.24 applications of cUC. The results suggest that cUC used as an adjunctive tissue therapy in conjunction with surgical debridement, resection of infected bone, open cortex, and antibiotic treatment may be an effective overall treatment strategy to promote wound healing of complex foot ulcers associated with osteomyelitis. The preliminary results are encouraging and warrant further randomized control studies to determine whether cUC might help address such an unmet medical need.